Intermittent Systems at Small Scale: Execution Model and Design Guidelines - Kim, Youngbin; Lim, Yoojin (2025 62nd ACM/IEEE Design Automation Conference (DAC), 2025)
Intermittent systems require software support to execute tasks amid frequent power failures. In designing such techniques, software designers rely on execution models that abstract hardware-level operations. In this paper, we propose an execution model that more accurately describes emerging intermittent systems with small energy storage. Our evaluation shows show that systems designed based on the traditional models can be up to 5.62 x less power-efficient than expected and may result in unsafe checkpoint operations. Our design guidelines enhance the performance of existing static and dynamic checkpoint techniques by 3.04 x and 2.85 x on average, respectively.